¿Otra infección urinaria o algo más? - Iolanda Oliveira; Sofia Calaça; Mariana Soares; Andreia Bernardino (Sociedade Galega de Medicina Interna, 2021)
Urinary tract infection (UTI) affects mostly women. Any condition that allows stasis or urinary obstruction predisposes to the development of UTI. The authors report the case of a 37-year-old woman with a recurrent UTI who presented with right lumbar pain irradiating to homolateral inguinal region and genito-urinary symptoms, and a pelvic extensive lesion was shown in the abdominal-pelvic CT in apparent relationship with L5 nerve root compatible with a Schwannoma. Schwannomas are usually benign tumors that rarely present malignant transformation. Repetitive UTIs may be a consequence of the mass effect or of neurological cause secondary to intraspinal schwannomas that cause urinary retention. Local recurrence or malignant change is possible, so complete tumor resection is important.